PENGUATAN LITERASI, NUMERASI, DAN ADAPTASI TEKNOLOGI PADA PEMBELAJARAN DI SEKOLAH: (Sebuah Upaya Menghadapi Era Digital dan Disrupsi) - Mar'atun Khasanah; Anggi Monica Putri; Darwanto D (Eksponen, 2021)
Strengthening literacy, numeracy, and technological adaptation are important efforts to improve the quality of human resources in the Digital Age and the Era of Disruption. Indonesia is very far behind other countries in this capacity. The government as well as related parties (Schools, Universities, Education Quality Assurance Institutions, and Parents) must participate in strengthening literacy, numeracy, and technology adaptation for students and educators in Indonesia. One of the activities is to integrate literacy, numeracy, and technology activities in learning either at school or at home.